Business management and ethics : insights from Indian ethos - Jeyanthi, P. Mary; Rajpurohit, Niranjan; Hack-Polay, Dieu (Emerald Publishing Limited, 2025)
While much research on business and management draws on Western perspectives, there is a dearth of literature that draws on other global perspectives and teachings. Business Management and Ethics: Insights from Indian Ethos draws from the wisdom available in ancient Indian scriptures and philosophies, which act as guides for students and future managers in decision-making. Business Management and Ethics provides insights in aligning modern day management education with more holistic and eastern perspectives to be used by teachers, students and scholars alike. Some of the key features of the book are a focus on management lessons from the Indian scriptures, Indian philosophies and approaches to ethical dilemmas, and a holistic approach to the integration of business ethics and management.
Keywords: Industrial management -- India.; Business ethics -- India.; Business & Economics -- Business Ethics.; Business ethics and social responsibility.; elektronické knihy; electronic books